The Role of Training Management in The Development of Human Resources in The Era of Industrial Revolution 4.0 - Siti Aisah; Anisa Junianti; Sonya Pita Lestari; Riyan Mirdan Faris; Kurniawan; M. Andri Juniansyah (Future Science, 2020)
Introduction: Training is often seen as an activity that is commonly carried out on employee performance. To create quality employee performance with training can help the success of a company. The company's goals are expected to be achieved with high employee performance. In the era of Industry Revolution 4.0, it is very important if Human Resources are further improved. Through this training management, the company can improve employee performance and the quality of human resources owned by the company so that they can compete in the industry 4.0 Revolution Era. Because of this, based on the research background above, training management plays an important role in improving the development of Human Resources in the Industrial Revolution Era 4.0 So that with the existence of training management in the Industrial Revolution Era, human resources will be of higher quality and can develop better in every company by keeping up with the increasing times. Methods: In writing this journal using a literature review, which contains the results of the researchers' thoughts on the theories in articles, journals, books, etc. which are following the research topic. Literature reviews use qualitative methods which only emphasize definitions, concepts, and focus more on case studies or theoretical adjustments to problems that occur in a given scope. The literature review was used as a reference in this study, namely international journals and national journals. Results: Based on the results obtained from several literature reviews, this training management played an important role in the development of Human Resources in the Industry 4.0 Revolution Era. because the era of the industry 4.0 revolution, was characterized by the need for digital skilled human resources to support the application of industry 4.0. Therefore, training management plays an important role in the development of Human Resources in the Industrial Revolution Era 4.0 as the main asset to create quality Human Resources so they can compete. Discussion: Management training in the development of Human Resources in the Industrial Revolution Era is a problem that must be studied and continuously improved so that Human Resources are skilled at technology and can compete and have quality.